2006
DOI: 10.1016/j.jfineco.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of collateral☆

Abstract: This paper is the sole responsibility of its authors and the views presented here do not necessarily reflect those of the Banco de España. We much appreciate the detailed comments made by an anonymous referee and Julio Segura, which have helped us to improve the paper significantly. Moreover, we thank everyone at a CEMFI seminar for their numerous comments and suggestions, in particular, M. Arellano, S. Bentolila, O. Bover and R. Repullo. Comments from participants at the Second International Conference on Cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
257
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(286 citation statements)
references
References 37 publications
20
257
3
4
Order By: Relevance
“…It therefore follows that commercial banks which extend relatively higher levels of credit are likely to incur lower non-performing loans. It is important to note that our results are contrary to most of researchers such as Jimenez et al (2005); Lis et al (2000) and Sinkey and Greenwalt (1991) However, similar findings are reported by Pasha and Khemraj (2009) and Al-Smadi and Ahmad (2009).…”
Section: Regression Analysiscontrasting
confidence: 91%
See 1 more Smart Citation
“…It therefore follows that commercial banks which extend relatively higher levels of credit are likely to incur lower non-performing loans. It is important to note that our results are contrary to most of researchers such as Jimenez et al (2005); Lis et al (2000) and Sinkey and Greenwalt (1991) However, similar findings are reported by Pasha and Khemraj (2009) and Al-Smadi and Ahmad (2009).…”
Section: Regression Analysiscontrasting
confidence: 91%
“…Salas and Saurina (2002) revealed that real growth in GDP explain variations in NPLs. Jimenez et al (2005) provide evidence that NPLs are determined by high real interest rates and lenient credit terms in addition to GDP of the economy. Al-Smadi and Ahmad (2009) found that inflation creates a substantial negative impact on credit risk.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Using Spanish bank-level data, Salas and Saurina (2002) finds that economic shocks are quickly transmitted to Spanish banks. Employing a similar framework, Jimenez and Saurina (2006) observes that collateral requirements are significantly compromised during a business upturn, fuelling a lending boom. Focusing specifically on the subprime episode, Dell'Ariccia et al (2008) finds that lending standards tend to be compromised more in areas that experienced larger credit booms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Economic prosperity reduced the probability of a potential bank crisis, which usually comes along with loan risk during economic recessions. On the other hand, loan losses can occur during economic booms if high growth GDP rates promote optimistic evaluations over borrowers' creditworthiness leading to less stringent policies, and when competitive structures make managers more willing to risk-taking activities (Jimenez and Saurina, 2006). Boyd et al (2004) underscore inflation as another key determinant of bank failure.…”
Section: Macroeconomic Variablesmentioning
confidence: 99%